Analysis of Production Quality Control in Minimizing Product Defects with the Six Sigma Method (Case Study at PT. Jaykay Files Indonesia) - Ermayana Ermayana; Jeni Sofyan Nur Rosyad (Institut Teknologi Bisnis AAS Indonesia, 2021)
PT. JayKay Files Indonesia is a company engaged in the industry that produces files and drills. Where the products have been exported to various countries and the quality is well received by various overseas customers. PT. JayKay Files Indonesia is certified with ISO 9001:2008, OHSAS 18001:2007 and ISO 14001-2004 environmental management system. However, to maintain this quality, the company must control the existing defective products. Then the research was carried out using the Six Sigma DMAIC (Define Measure Analyze Improv Control) stage. And produced 4 (four) types of defects in the Define stage, with the calculation of the sigma value of 3.8 with 3.8% damage at the measure stage, then Analyze which occurs because there are several causes using a fishbone diagram, namely machine, human, method and environmental factors. At the improve stage, there are several recommendations for improvement so that for control, supervision is carried out at the dept. Quality control.